Comprehensiveness of Experiential Learning Programme of Indian Council of Agricultural Research (ICAR) implemented in Indian Agricultural Universities - LEKANG, BUSHE; NAIN, M S; SINGH, RASHMI (The Indian Journal of Agricultural Sciences, 2017)
Education, either formal or non-formal has been viewed as the pillar for human development. Central to the education system is the curriculum which determines what is taught, how it is taught what resources are needed for attaining its objectives. Indian Council of Agricultural Research introduced a programme in 2006 on Experiential Learning Programme aimed at equipping undergraduates with entrepreneurial skills. Alongside the programme, a curriculum was developed to instill entrepreneurial knowledge, attitudes, skills and culture among agricultural undergraduates. This has study undertaken to evaluate the performance of comprehensive Experiential Learning Programme curriculum. The curriculum has been in vogue since a decade hence its evaluation comes at a rightful time. An exploratory research study was conducted in six purposively selected agricultural universities in North India among students and a desk review aimed at finding out how comprehensive the curriculum was. Findings revealed that majority of students were aged between 20 and 24 years, first born, rural background, general caste and males except for home science which had 100% females. Course content was generally perceived to be relevant and adequate. The credit hours showed that the curriculum emphasized on both knowledge and skills development. The courses with the curriculum provided basic knowledge and skills on management, economic concepts, communication, marketing, technology, numeracy, legal aspect, support system and research skills which are needed for entrepreneurship development. To continue instilling entrepreneurial knowledge, skills and attitudes among agricultural graduates the curriculum should therefore be maintained.